EFEITO DA FARINHA DA CASCA DE MARACUJÁ NO PESO E NO ÍNDICE GLICÊMICO DE RATOS - Francine Buzzato Lage; Heid Mara Machado Guerra; Naira Correia Cusma Pelogia (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
The fiber intake is an alternative to weight control. The objective of this experiment was to determine the effect of pectin, present in passion fruit peel, on weight change and glucose. Have been used 35 male Wistar rats divided into four groups. The Control group received water and food (n=09); The passionfruit group received food plus passion fruit peel (n=09); The hyper caloric group received cafeteria diet (n=08); The hyper caloric + passion fruit group received caloric diet increased with passion fruit peel (n=09), over 21 days. The weight of the animals was measured once a week and blood glucose was measured in the first week and at the end of the experiment. The difference in weight was analyzed with ANOVA, a criterion, followed by Bonferroni's test; was adopted significance level of 5% (p<0.05). Was observed reduction in weight gain in the passion fruit group in comparison with the control group and increased weight gain in the hyper caloric and hyper caloric + passion fruit groups, between the beginning of the experiment and the 1st week of treatment. Between the 2nd and 3rd week of treatment, the hyper caloric group had an increase in body weight compared with the other groups. The weight gain in the passion fruit group and hyper caloric + passion fruit group did not differ from the control group. The glycemia (mg/dl) at the end of the experiment was higher in hyper caloric and hyper caloric + passion fruit group than in the control and passion fruit groups. We conclude that the passion fruit peel flour associated with hyper caloric diet reduced weight gain, but insufficient to reduce glycemia.